CFRT is involved in colorectal cancer stem cell phenotype - Palma, Alejandra Graciela (2019)
CFTR is a chloride channel expressed in many epithelial cells and there is a relationship between this channel and cancer. The cancer stem cells (CSC) are responsible of tumorigenesis, secondary focus formation in metastasis and chemoresistance. We previously found that CFTR is expressed in colorectal cancer cells HCT116 and is associated with cancer stem cells (CSC). To further investigate this, we inhibited CFTR activity with CFTR inhibitor-172 or downregulated CFTR expression with two different shRNA (shCFTR1 or shCFTR2) in HCT116 cells. When these cells were transfected with the shCFTRs, we observed a downregulation of both CFTR protein and mRNA by Western blot, immunofluorescence and RT-PCR. Then we determined the clonogenic growth, a property of CSC, of control HCT116 cells and when CFTR is inhibited after seven days of platting at low density. The number of colonies was diminished in cells where CFTR was inhibited (p<0.05). Next we analyzed the expression of CSC markers in these cells. A lower amount of the colon cancer stem cell marker CD133, Nanog, cMyc and Oct-4 were detected by immunofluorescence staining of HCT116 cells when CFTR is inhibited. From these and our previous results we confirmed that the channel CFTR expression and activity are associated with CSC, indicating that CFTR could have an influence on the CSC properties at least in human colorectal cancer.